ANALISIS DIGITAL FORENSIK SPEAR PHISHING MENGGUNAKAN METODE NATIONAL INSTITUTE OF JUSTICE (NIJ) : Studi Kasus Instagram Verified Account - Aris Dwi Prasetyo (2022)
The rapid development of technology has an impact on the use of social media. Social media can facilitate interaction between users as a tool for disseminating information about a person or an existing brand. Everyone tries to get all the attention that exists on a social media platform like Instagram. But this has risen a new negative impacts such as account fraud, theft of personal data, and the act of selling accounts that have been hacked by hackers. The type of crime that often occurs is Phishing, which is a scam that seems to display the exact same thing as the original platform. In 2020 there were a total of 2549 cases of Phishing crimes that occurred in Indonesia and in 2021 there were 264 cases. One way to analyze digital evidence that can later be used as trial evidence is by digital forensics. This activity facilitates the search for digital evidence. In this study, researchers will conduct a digital forensic analysis related to spear phishing crimes using methods that have been proposed by the National Institute of Justice (NIJ). In this method, the stages that will be carried out include Preparation, Collection, Examination, Analysis, and Reporting. Based on research, it was found that the phishing pages used by perpetrators with the domain of the instagram-page-login.herokuapp.com page and the IP Address used were 18.208.60.216 and 54.165.58.209.